Quality Control Analysis of The Water Meter Tools Using Decision-On-Belief Control Chart in PDAM Surya Sembada Surabaya - Farida Agustini Widjajati; Nuri Wahyuningsih; Lisda Septi Hasofah (LPPM Institut Teknologi Sepuluh Nopember, 2016)
Efforts to maintain and improve the quality of the resulting product can be done by using statistical quality control. One of the methods used in quality control is DOB (Decision On Belief) control chart. DOB control chart is a controller diagram which is used in quality control of univariate data. In this paper, we discuss quality control of the water meter tools using DOB control chart. The case study is in PDAM Surya Sembada Surabaya. Production quality control can also be applied to the c univariate control chart to compute the sensitivity of DOB control chart. Implementation of c control chart and DOB control chart indicates that the data of water meter tools have not been statistically controlled. Application of DOB control chart provides results that are more sensitive by 23.33% than c control chart based on the amount of data that is out of control.